Drawing Planar Graphs with Large Vertices and Thick Edges - Barequet, Gill; Goodrich, Michael; Riley, Chris (Journal of Graph Algorithms and Applications, 2004)
We consider the problem of representing size information in the edges and vertices of a planar graph. Such information can be used, for example, to depict a network of computers and information traveling through the network. We present an efficient linear-time algorithm which draws edges and vertices of varying 2-dimensional areas to represent the amount of information flowing through them. The algorithm avoids all occlusions of nodes and edges, while still drawing the graph on a compact integer grid. <!—->